A theoretical analysis of interface debonding for coated sphere with functionally graded interphase - Ben, S.; Zhao, J.; Rabczuk, T.
We present a novel nonlinear cohesive law for coated sphere with functionally graded interphase (FGI). It is derived from the van der Waals interaction accounting for the interface debonding of the coated sphere subjected to radial tensile loading. The present analytical results show that: (1)Higher values of the interphase radius rb lead to a higher interface strength and a higher debonding strain; (2)a higher Young's modulus Ef and the Poisson's ratio vf of the sphere lead to a lower interface strength and a smaller debonding strain; (3)large values of the index n and the inner Young's modulus Ea of FGI as well as the Poisson's ratio vm of the entire coat improve the interface strength and reduce the debonding strain; (4)the sphere radius ra and the outer coat radius rc can not only improve but also reduce the interface strength and the debonding strain, respectively. The established analytical solutions should be of great help for understanding the mechanical properties of the coated sphere and sphere-reinforced composites, designing microcomposites and microelectromechanical systems.
Keywords: COAT; COHESIVE LAW; INTERPHASE; MATRIX; SPHERE